Implementation of Job Training Program on Employee Performance at PT Worldwhite Enterprise Brand Prepp Studio - Musyaffa, Fadhel; Pratama, Muhammad Dzaqi; Digdowiseiso , Kumba (CV ODIS, 2024)
This research discusses the implementation of job training programs on employee performance at PT World White Enterprise Brand Prepp Studio, a company operating in the creative industry. The main focus of this research is to analyze the effectiveness and impact of the training program that has been implemented by the company in improving employee skills and performance. This research methodology includes analysis related to training sourced from several previous studies. The research results show that the training program has made a positive contribution to increasing employee productivity and competency. With this program, employees are able to face work demands more efficiently and have a positive impact on the company's production results. In addition, this research also evaluates employee responses and perceptions of the training program, which can be a basis for improving and developing the program in the future. The implications of these findings can help PT World White Enterprise Brand Prepp Studio and similar companies to design more effective training programs, in accordance with industry needs and developments. This study provides insight into the importance of investing in human resource development to achieve competitive advantage in a dynamic business environment.